Fuzzy generalised predictive control for a fractional‐order nonlinear hydro‐turbine regulating system. Issue 14 (21st September 2018) - Shi, Ke; Wang, Bin; Chen, Haoyong
Abstract : This study focuses on a fuzzy generalised predictive control method for a fractional‐order hydro‐turbine regulating system (HTRS). Based on the Grünwald–Letnikov (G–L) definition of fractional calculus and discretisation, the fractional‐order hydraulic servo system is transformed into the standard controlled autoregressive integrating moving average (CARMA) model. With the help of fuzzy linearisation theory, the fuzzy predictive model of the integer‐order part of the HTRS is presented. Furthermore, by using the fourth‐order Runge–Kutta algorithm, the obtained fuzzy predictive model can be easily transformed into the CARMA model. Then, based on the overall CARMA model and the generalised predictive control theory, a novel nonlinear fuzzy generalised predictive controller is designed for the fractional‐order HTRS. Finally, numerical simulations are implemented to verify the validity and superiority of the proposed method. It also provides a reference for relevant hydropower systems.